Assessment of Serum Vitamin D3 and Vitamin B12 Levels in Iraqi Women with Osteoporosis A Cross-Sectional Study - Naji, Zainab Abdul Wahed (American Journal of Bioscience and Clinical Integrity, 2025)
Background: Osteoporosis is a degenerative bone disease marked by a significant reduction in bone mineral density and a heightened susceptibility to fractures, particularly among postmenopausal women. Nutritional deficiencies, including those of vitamin D3 and vitamin B12, have been implicated in the pathogenesis of osteoporosis. The present study seeks to evaluate serum levels of vitamin D3 and vitamin B12 in postmenopausal women with osteoporosis compared to healthy controls and explore their correlation with age and BMI. Material and Methods: This cross-sectional case-control investigation enrolled 68 postmenopausal women, stratified equally into osteoporotic and control cohorts according to their DEXA-derived T-scores. Serum levels of 25-hydroxyvitamin D3 and vitamin B12 were measured using CLIA and ECLIA, respectively. Statistical analyses included t-tests and Pearson correlation, with significance set at p < 0.05. Results: Osteoporotic women had significantly lower mean serum vitamin D3 (16.8 ± 5.7 ng/mL) and vitamin B12 levels (221.3 ± 49.6 pg/mL) compared to controls (26.1 ± 6.4 ng/mL and 287.9 ± 56.8 pg/mL, respectively; p < 0.001 for both). Vitamin D3 and B12 levels showed positive correlations with BMI (r = 0.44 and r = 0.41) and negative-correlations with age (r = –0.36 and r = –0.33). A moderate positive-correlation was detected between vitamin D3 and B12 levels (r = 0.39, p = 0.003). Conclusion: Postmenopausal women with osteoporosis exhibit significantly-lower levels of vitamin D3 and B12. Their deficiency correlates with lower BMI and advancing age, emphasizing the importance of routine nutritional assessment and targeted supplementation to mitigate osteoporosis risk.